Penerapan Teknologi IoT pada Sistem Monitoring Tekanan Ban Mobil yang Berjalan - Hendy Briantoro (P3M Politeknik Negeri Bengkalis, 2022)
There are many vehicle accidents on the road, around 18-23% are caused by tire burst. One solution is to monitor the car tire pressure. In this study, we created a car tire pressure monitoring system that runs using IoT technology. This system successfully monitors tire pressure changes remotely.